1978
DOI: 10.1021/ja00479a023
|View full text |Cite
|
Sign up to set email alerts
|

The molybdenum site of nitrogenase. Preliminary structural evidence from x-ray absorption spectroscopy

Abstract: One of the two protein components of the nitrogenase enzyme system (the so-called MoFe protein) contains two Mo atoms and 24 -32 Fe atoms per 220-270 000 molecular weight. Despite many hypotheses about the Mo site and its involvement in dinitrogen reduction, there has been no spectroscopic means of unambiguously probing the state of Mo. In this paper, the results of x-ray. absorption spectroscopy studies are described and the analysis of these results provides the first direct evidence of the Mo coordination e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
97
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 229 publications
(106 citation statements)
references
References 7 publications
9
97
0
Order By: Relevance
“…The method of curve fitting (8,10,12) is very useful to more fully resolve the frequency components of EXAFS data, especially in cases of multiple shells of scatterers (12). The procedure for carrying out a curve-fitting analysis is first to fit the data with one shell of a chemically reasonable atom type.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method of curve fitting (8,10,12) is very useful to more fully resolve the frequency components of EXAFS data, especially in cases of multiple shells of scatterers (12). The procedure for carrying out a curve-fitting analysis is first to fit the data with one shell of a chemically reasonable atom type.…”
Section: Resultsmentioning
confidence: 99%
“…If this single shell does not adequately describe the EXAFS, then a second shell is added. Experience has shown that up to four or so different shells may be fit to good data on a k range of [4][5][6][7][8][9][10][11][12] A-' before correlation problems become so severe as to render the results unreliable. The type of scatterer atom chosen for a given shell can be tested by using the pairwise phase parameters for a different scatterer type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molybdenum complexes containing Mo--S and Mo--N bonds are of special interest because of their relevance to a variety of molybdenum-containing enzymes (Cramer, Hodgson, Gillum & Mortenson, 1978) and hydrodesulfurization catalysts (Anzenhofer & de Boer, 1969 Tiripicchio-Camellini & Lahoz, 1986). During our studies of molybdenum-sulfur complexes with molybdenum in a low oxidation state, we obtained several complexes with pyS in different coordination modes.…”
Section: Commentmentioning
confidence: 99%
“…Molybdenum complexes containing Mo--S and Mo--N bonds are of special interest because of their relevance to a variety of molybdenum-containing enzymes (Cramer, Hodgson, Gillum & Mortenson, 1978) and hydrodesulfurization catalysts (Anzenhofer & de Boer, 1969). To our knowledge, (C8H20N)[Mo2(C5H4NS)(CO)9] molybdenum complexes containing Mo--S and Mo--N bonds involving a pyridine-2-thiolato (pyS) moiety as a mixed bidentate (N,S) ligand have not been reported in the literature, although many Group VII and Group VIII metal complexes with pyS ligands are known (Demming, Meah, Bates & Hursthouse, 1988;Oro, Ciriano, Viguri, Tiripicchio, Tiripicchio-Camellini & Lahoz, 1986).…”
Section: Commentmentioning
confidence: 99%